Shutdown Contests in Multi-Plant Firms and Governmental Intervention - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
When a multi-plant firm must close one unit due to declining demand it can choose between two alternatives. On the one hand, the firm can announce a certain span of time in which the plants are evaluated according to relative performance with the least performing plant being shut down in the end (shutdown contest). On the other hand, the firm can use given information on the plants' productivities and close the least productive unit. This paper analyzes the selection and incentive properties of both alternatives. Multi-plant firms often operate in an international industry. Hence, in a second step we discuss the effects of governmental support for domestic plants on selection efficiency.
Keywords: D21; D61; F23; F51; J65; 330; auction; collective tournament; plant closing; governmental intervention; Produktionsanlage; Liquidation; Multinationales Unternehmen; Extensives Spiel; Wirtschaftsförderung; Auktion; Standortwettbewerb; Theorie